MCNP Dose Analysis for the Iranian Plasma Focus Neutron Source - Noonbede, Masome; Kasesaz, Yaser; Khakshournia, Samad; Damideh, Vahid (Springer US, 2015)
The equivalent and effective doses from the first Iranian 115 kJ Mather type Plasma Focus machine (IRMPF- 100) have been calculated for the analytical ORNL modified adult phantom in 12 body organs using MCNP4C Monte Carlo code. The largest doses are related to spleen in PA other than lungs, and testes in AP orientation. The largest values in RLAT and LLAT orientations are related to right and left lung, respectively. AP orientation appears with the largest effective doses stemming from the contribution due to exposure of the testes. It is demonstrated that the effective dose due to neutrons for people working with the PF is well within the relevant dose limits. Differences of approximately 10 % are observed in the obtained results for the effective dose between a bare source of neutrons and the realistic situation in which electrodes, chamber wall and concrete floor are included in the MCNP simulation.